Current understanding of antimicrobial resistance mechanisms in bacteria (analytical review) - O. V. Pruntova; V. S. Russaleyev; N. B. Shadrova (Ветеринария сегодня)
Data on mechanisms of resistance to antimicrobials in bacteria are reviewed and summarized. Main causes of resistance emergence and spread in bacteria are analyzed. Mechanisms of innate resistance of pathogenic bacteria (non-specific efflux pumps, antibiotic-inactivating enzymes and mechanisms serving as permeability barriers) are characterized. Mechanisms of acquired resistance are described: antibiotic modification or degradation; active removal of an antimicrobial from a bacterial cell – efflux (draining out); sequestration; target modification (bypass). The origin of antimicrobial resistance mechanisms in pathogenic bacteria is shown to be debatable. It is noted that producer microorganisms can directly transfer antimicrobial resistance genes to pathogenic bacteria, but a reliable link between this process and antimicrobial resistance spread has not been identified and proven so far. Horizontal gene transfer, including free DNA transformation, transduction by bacteriophages and plasmid-involving conjugation, is believed to play an important role in antimicrobial resistance spread. All three mechanisms are widespread in nature, although some bacterial species use one mechanism to a great extent than the other two. Transduction is supposed to play an important role, in particular, in the antibiotic resistance gene transfer, but the significance of transformation or transduction in the resistance gene transfer under the laboratory or environmental conditions has not been clarified so far due to the difficulty of naturally emerging recombination detection. Data on the role of conjugation in the antimicrobial resistance gene spread in nature, in particular carbapenem- and quinolone-resistance genes in gram-negative and gram-positive bacteria are presented. New trends in the antimicrobial resistance gene spread are indicated.